Social work interview - Alfred Kadushin; Kadushin Goldie (New Delhi Rawat Publications, 2015)
General orientation and basic concepts of interviewing and communication; interview as communication; listening and silence as interview techniques; nonverbal communication; establishing a relationship; problem exploration phase; developmental phase; part three special problems in interviewing.
Keywords: Social work